KETENTUAN PREMI ASURANSI SEBAGAI JAMINAN TERHADAP PEMBIAYAAN MURABAHAH PADA PERBANKAN SYARIAH - Hidayatina, Hidayatina (JURIS (Jurnal Ilmiah Syariah), 2015)
Murabaha financing is a form of financing which is provided by sharia banking. However, murabaha financing  can be granted by Islamic banks only at the risk of default on the part of the customers. Therefore, Islamic banks are allowed to require security to customers. One of the requirements is that the customers should submit a number of insurance premium amounts depending upon how much the ceiling of financing provided to customers, However, the implementation of provisions of the insurance premium is not suitable with the provision of guarantees and insurance concepts in Islamic economy. Such mechanism is not approved by sharia insurance fund forfeited as it is found in conventional insurance. It implies that if the customers of murabaha financing has fulfilled their obligations to pay the mortgage financing (he did not pass up defaults or die), they should get the collateral back since their debts have fully repaid.Kata kunci: premi, murabahah, perbankan syariah